Association of body mass index and gross national income with caries experience in children in 117 countries. (18th May 2020) - Al-Ansari, Asim; Nazir, Muhammad Ashraf
Abstract: Objective: To evaluate the association of body mass index (BMI) and gross national income (GNI) per capita with dental caries experience in children at population levels. Methods: This ecological study used global data of decay, missing, and filled teeth (DMFT), BMI, and GNI. DMFT data of 12 years old children from 117 countries were obtained from the World Health Organization. BMI data of children and adolescents from the same 117 countries were retrieved from the NCD Risk Factor Collaboration and GNI per capita from the World Bank. ANOVA test, Pearson's correlation coefficient (r), and multivariable linear regression were performed. Results: Globally mean BMI ranged from 16.1 to 22.2 in children. Low-income countries had the lowest BMI (17.41 ± 0.57) and high-income countries had the highest BMI (20.14 ± 0.87) ( p < .001). The highest mean DMFT was observed in upper-middle-income countries (2.48 ± 1.16) and the lowest in low-income countries (1.22 ± 0.83) ( p = .001). There was no significant correlation between BMI and dental caries (DMFT) ( r = .063; p = .498). However, there were significant correlations between GNI per capita and BMI ( r = 0.366; p < .001) and GNI per capita and DMFT ( r = −0.252; p = .007). In multivariable linear regression, GNI per capita was negatively associated with caries experience in children (B= −1.83; p < .001). Conclusion: The study found that BMI was associated with income levels of the countries. GNI per capita significantly and negatively correlated with DMFT in children. Further investigation into the association between BMI and dental caries is warranted.